Antimicrobial resistance of foodborne pathogens in retail pork - Apostolou, Dina (2019)
The risk of potential transmission of antimicrobial resistance in bacteria from animals to humans via the food chain needs to be extensively evaluated. Retail pork products, including organic, non-organic and free-range, were purchased from four different sources and tested, along with pig carcass swabs taken from a small local non-commercial abattoir, for the presence of multidrug-resistant (MDR) E. coli, Salmonella, Staphylococcus aureus and Yersinia enterocolitica. Isolation methods were based on the ISO standards for each organism but some method variations were tested to improve isolation frequency. Eight Escherichia isolates were detected, six of which were identified as E. coli, twelve Yersinia isolates with six being identified as Yersinia enterocolitica, five as Yersinia frederiksenii and one as Yersinia sp. A total of four Gram positive coccoid isolates were detected with two identified as Staphylococcus aureus. No Salmonella isolates were obtained. All isolates were tested for phenotypic resistance using disc diffusion assays and antibiotic discs from fifteen antibiotic classes. Five of the eight Escherichia isolates, 12/12 Yersinia isolates and 1/3 Staphylococcus isolates were resistant to three or more antibiotics from different classes and so could be defined as MDR. Resistances observed among E. coli isolates include ampicillin, ampicillin/clavulanic acid, sulphonamides, streptomycin, tetracycline and chloramphenicol, while in Yersinia isolates resistances observed were to ampicillin, ampicillin/clavulanic acid, cefoxitin, cefpodoxime, sulphonamides and nitrofurantoin. PCRs were performed and all Escherichia and Yersinia isolates were positive for the possession of chromosomal AmpC. Staphylococcus isolates were tested for the presence of the mecA gene conferring resistance to methicillin but none showed possession of the gene. PCR was also performed for Staphylococcus isolates to detect if they were CC398 strains but none were. Gram-negative isolates were also tested for metal resistance using PCR for the detection of merA, merC and intl1 genes associated with mercury resistance, pcoE gene for copper resistance and silE and silP genes for silver resistance. Only two E. coli isolates were shown to possess genes associated with metal resistance. Escherichia isolates were tested for the presence of the pathogenic eae, astA, heat-labile (LT) and heat-stable (ST) toxin genes. Five of the eight Escherichia isolates tested positive for the possession of enteroaggregative astA gene and none tested positive for the rest of the genes. Yersinia isolates were tested for the chromosomal ail and inv pathogenic genes and for the virulence plasmid genes yadA and virF. All Y. frederiksenii tested positive for the possession of yadA gene and 2/5 Y. frederiksenii were positive for the ail gene, findings that are quite unusual since both genes are associated with pathogenic Yersinia. None of the Y. enterocolitica isolates showed possession of any pathogenic genes. This study demonstrated the possible transmission of MDR foodborne pathogens to humans via the food chain.